Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Multifinance Non Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 - 2022 - Pebrianti, Sriayuni; Sudrajat, Ayi Mohamad (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
Earnings management is the choice made by managers in determining accounting policies, or real actions, that influence profits so as to achieve targets by reporting certain profits. This research aims to determine the effect of profitability, liquidity and company size on earnings management partially and simultaneously in non-banking multi-finance companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The type of research used is quantitative, with a sampling technique using purposive sampling from a total of 19 companies with a total of 57 samples obtained from 19×3 years. The data used in this research is secondary data, namely financial reports. The method used in this research is descriptive statistical analysis method with multiple regression analysis using the SPSS version 25 application. The results of this research show that partially the profitability and liquidity variables have a positive and significant effect on earnings management with a sig value of 0.000 < 0.05, and a sig value of 0.002 < 0.05. The company size variable has no effect on earnings management with a sig value of 0.944 > 0.05. Meanwhile, simultaneously the profitability, liquidity and company size variables have a significant effect on the earnings management variable with a sig value of 0.000 < 0.05. The results of the correlation coefficient test (R2) obtained a value of 50.5% in explaining earnings management. Meanwhile, the remaining 49.5% is explained by other factors outside the independent variables studied.   Keywords: Profitability,Liquidity,Firm ,Earnings Management